Chemopreventive and therapeutic potential of chrysin in cancer: mechanistic perspectives. Issue 2 (4th March 2015) - Kasala, Eshvendar Reddy; Bodduluru, Lakshmi Narendra; Madana, Rajaram Mohanrao; V, Athira K.; Gogoi, Ranadeep; Barua, Chandana C
Highlights: Short account on role of chrysin in multistep carcinogenesis process. Chemopreventive and therapeutic studies of chrysin in cell lines and animal models. Succinct description of mechanistic perspectives of chrysin. A colossal narration of effect of chrysin on signalling pathways and molecular targets. Brief note on pharmacokinetics of chrysin. Abstract: Chrysin, a naturally occurring flavone, abundantly found in numerous plant extracts including propolis and in honey is one of the most widely used herbal medicine in Asian countries. Nowadays, chrysin has become the foremost candidate exhibiting health benefits, owing to its multiple bioactivities such as antioxidant, anti-inflammatory, anti-allergic, anti-diabetic, anti-estrogenic, antibacterial and antitumor activities. Anticancer activity is most promising among the multiple pharmacological effects displayed by chrysin. In vitro and in vivo models have shown that chrysin inhibits cancer growth through induction of apoptosis, alteration of cell cycle and inhibition of angiogenesis, invasion and metastasis without causing any toxicity and undesirable side effects to normal cells. Chrysin displays these effects through selective modulation of multiple cell signaling pathways which are linked to inflammation, survival, growth, angiogenesis, invasion and metastasis of cancer cells. This broad spectrum of antitumor activity in conjunction with low toxicity underscores the translational value of chrysin in cancer therapy. The present review highlights the chemopreventive and therapeutic effects, molecular targets and antineoplastic mechanisms that contribute to the observed anticancer activity of chrysin.